The makings of a terrorist: continuity and change across left-, right- and jihadist extremists and terrorists in Europe and North-America, 1960s-present - Schuurman, Bart (Deviant behavior, 2023)
This article conducts comparative research to advance our understanding of the causes of terrorism. Primarily, by assessing differences and similarities between left-, right- and jihadist extremists and terrorists, the prevalence of certain variables amongst populations of radicalized individuals will be determined. Secondly, by contrasting, where possible, these prevalence rates with representative samples from the broader population, the distinctiveness of these biographical details amongst extremists and terrorists is discussed. The article compares the Analysen zum Terrorismus, one of the most comprehensive studies of (left-wing) terrorism ever conducted, with original empirical work on contemporary right-wing and jihadist extremism and terrorism. Results suggest that extremists and terrorists from these contexts are not distinctive in terms of socio-economic backgrounds, educational achievements, criminal antecedents or suicide attempts. There does appear to be a higher prevalence of unemployment, broken homes and related childhood stressors. The importance of social movements and groups in drawing and anchoring individuals to extremism and terrorism is emphasized across ideological boundaries, as is the influence of societal and political contextual factors, such as political representation of extremist views.